Modelling Crater Formation and Gas Dispersion Following Buried Pipeline Ruptures - Paul Brasser; Rik Van Haaften; Andreas Mack (Chemical Engineering Transactions, 2025)
As environmental concerns continue to grow, storage of CO2, in depleted gas fields is an option. This requires transporting the CO2, which is commonly done through pipelines where it is liquefied under high pressure. In scenarios where a buried pipeline ruptures, pressurized gases are rapidly released, forming a crater and creating a significant dispersion risk. This paper introduces a crater formation model implemented in EFFECTS, a consequence modeling tool developed by Gexcon, that predicts both crater dimensions and the behavior of the exit jet for use in dispersion modeling. The Webber model is used for describing the release from the rupture of a long pipeline and integrating Cleaver and Defined Area models for the crater estimation. This study validates the model against both experimental data and real accident cases. Results show a good agreement between modeled and observed data. Sensitivity analysis is used to find the variables that influence outcomes the most.